2020
DOI: 10.1177/0032885520956394
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Prison Work: The Experience of Female Provincial Correctional Officers in Canada

Abstract: Drawing on the accounts of female correctional officers working in Canadian prisons, we explore how gender identity influences the work orientations and social relationships of female officers and their interpretations of working with male and female prisoners. We suggest that female officers tend to pursue correctional work in a way that incorporates traits culturally associated with femininity and that relies on gendered understandings of prisoners’ dispositions and needs. In general, female officers’ accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Although a previous study observed no significant difference in the rate of violence experienced by male and female prison employees (34), the current findings indicate that violence type may be influenced by gender. The experiences of women CWs are in line with concerns of gender inequality and sexism that appear in this male-dominated profession (35). These factors may partly explain why all the women in the study kept their webcams off while all the men kept theirs on.…”
Section: Work Culturesupporting
confidence: 62%
“…Although a previous study observed no significant difference in the rate of violence experienced by male and female prison employees (34), the current findings indicate that violence type may be influenced by gender. The experiences of women CWs are in line with concerns of gender inequality and sexism that appear in this male-dominated profession (35). These factors may partly explain why all the women in the study kept their webcams off while all the men kept theirs on.…”
Section: Work Culturesupporting
confidence: 62%
“…Dealing with emotional trauma calls for a different skill set that male COs struggle with due to different social expectations. They become less tolerant when dealing with female inmates, leaving the responsibility to female COs (Ricciardelli & McKendy, 2020).…”
Section: Masculine and Feminine Expectations And Rolesmentioning
confidence: 99%
“…However, this is understandable, it is due to sexual abuse history that female inmates struggle with trauma and unhealthy relationships with men (Correctional Investigator, 2021). Nevertheless, women are also expected to step in when working with male inmates without any restrictions meaning they work more for the same pay (Ricciardelli & McKendy, 2020).…”
Section: Gendered Policymentioning
confidence: 99%
“…Correctional officers (COs) perform their occupational responsibilities within a climate of continual carceral care, balancing relationships with colleagues 1 Memorial University of Newfoundland Marine Institute, St. John's, Canada and people who are incarcerated (PWAI), with other organizational and occupational duties (Ricciardelli & McKendy, 2020;Ricciardelli & Perry, 2016).Their work cultures are shaped by formal and informal processes (Ricciardelli & McKendy, 2020), each informed by shared meanings (Klofas & Toch, 1982;Lombardo, 1985;Rudes & Magnuson, 2019). Occupational culture, as defined by Farkas and Manning (1997), refers to "the values, beliefs, material objects and taken-for-granted knowledge associated with a full-time occupational role" that "serves to mediate, buffer, and otherwise pattern the conflicts" members of an occupational group face (p. 57).…”
Section: Introductionmentioning
confidence: 99%
“…Correctional officers (COs) perform their occupational responsibilities within a climate of continual carceral care, balancing relationships with colleagues and people who are incarcerated (PWAI), with other organizational and occupational duties (Ricciardelli & McKendy, 2020; Ricciardelli & Perry, 2016). Their work cultures are shaped by formal and informal processes (Ricciardelli & McKendy, 2020), each informed by shared meanings (Klofas & Toch, 1982; Lombardo, 1985; Rudes & Magnuson, 2019).…”
Section: Introductionmentioning
confidence: 99%